Investigation of the performance of a new thermosyphon heat pipe design for applications heat transfer from liquid to gas - Gurturk, Mert; Kale, Cihangir; Kok, Besir (Pergamon-Elsevier Science Ltd, 2021)
In this study, two different new Thermosiphon Heat Pipes (THP) which have 25 and 40 mm diameter were designed. These designed THPs are intended to be used to transfer thermal energy from a heat source to the environment, taking into account the climatic conditions of a particular location. According to the theoretical calculations made within the scope of the study, design criteria were determined. The accuracy of these design parameters also was checked by experimental studies. The design parameters considered for 25 mm THP has the best results for many operation conditions. After proving the correctness of the strategy considered in the design, experiments were carried out for different operating conditions (air velocity, the temperature of air and heat source) for 25 and 40 mm THPs. The values of heat transfer coefficient in THPs considered within the scope of this study were calculated for both condenser and evaporator sections separately. It was observed that the heat transfer coefficient values in the evaporator section of 25 mm THP are better than the heat transfer coefficient values in the evaporator section of 40 mm THP. The values obtained in the condenser section vary between 6.84 <= h(c) <= 11.36 W/m(2) K for all operating conditions.
Keywords: Heat exchanger; Heat pipe; THP; Thermosyphon heat pipe